USM TO CONTINUE PROVIDING AN ECOSYSTEM OF EXCELLENCE IN R&I - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 14 January 2016 – Universiti Sains Malaysia (USM) will continue to provide an ecosystem of excellence for the development in Research and Innovation (R&I) to function as pathways for academicians to move forward in various areas of expertise that transcend disciplines.